6 Peer to peer leadership teaching for foundation doctors. (3rd November 2019) - Nye, Charles JS; Haggie, Rebecca LG; Sellers, Isabel; Zheng, Lynn; Smith, Iain; Slade, Mark
Abstract : Introduction: Foundation doctors often say they feel intimidated by the idea of 'leadership' and have received little teaching on the subject. We planned to address this using peer to peer teaching. This method has been shown previously to be a valuable learning experience for the participants and the facilitators. Method: We surveyed the Foundation doctors asking them how much leadership teaching they had previous had and to rank their confidence in their leadership abilities, how keen they were to develop and improve their leadership skills and whether leadership teaching is important and relevant for them as Foundation doctors. We arranged a peer led leadership teaching session for foundation doctors which consisted of several short workshops. These were 'difficult conversations', 'followership', 'resilience and how to develop in your team' and a 'senior doctors experience'. We then assessed whether it was an effective way to improve understanding and engagement in leadership by repeating the survey asking the same three questions. The Results were analysed using a two tailed paired T-test (n= 23, p <0.05). Results: Feedback from the facilitators and participants was positive. The mean rating by the participants was 4.4/5. Most trainees had received very little or no formal leadership teaching prior to the session (median = 0). The teaching session showed an improvement in all 3 areas assessed, notably in the confidence of participants in their leadership ability, increasing from 3.3/5 to 3.5/5 (p < 0.05). Conclusion: Our research illustrates the lack of formal leadership teaching for foundation doctors. This project demonstrates that peer to peer teaching is an effective way to help build confidence and understanding both for those who receive the session and those who organise it. We hope that our leadership teaching model will be replicated across other foundation schools in the UK.